FINANCIAL COST TO INSTITUTIONS ON PATIENTS WAITING FOR GALL BLADDER DISEASE SURGERY - Waqas, Ahmed; Qasmi, Shahzad Ahmed; Kiani, Faran; Raza, Ahmed; Khan, Khizar Ishtiaque; Manzoor, Shazia (Journal of Ayub Medical College Abbottabad, 2014)
Background: The aim of this study was to determine the financial costs to institution on patients waiting for gall bladder disease surgery and suggest measures to reduce them. Methods: This multi-centre prospective descriptive survey was performed on all patients who underwent an elective cholecystectomy by three consultants at secondary care hospitals in Pakistan between Jan 2010 to Jan 2012. Data was collected on demographics, the duration of mean waiting time, specific indications and nature of disease for including the patients in the waiting list, details of emergency re-admissions while awaiting surgery, investigations done, treatment given and expenditures incurred on them during these episodes. Results: A total of 185 patients underwent elective open cholecystectomy. The indications for listing the patients for surgery were biliary colic in 128 patients (69%), acute cholecystitis in 43 patients (23%), obstructive jaundice in 8 patients (4.5%) and acute pancreatitis in 6 patients (3.2%). 146 (78.9%) and 39 (21.1%) of patients were listed as outdoor electives and indoor emergencies respectively. Of the 185 patients, 54 patients (29.2%) were re-admitted. Financial costs in Pakistani rupees per episode of readmission were 23050 per episode in total and total money spent on all readmissions was Rs. 17,05,700/-. Conclusion: Financial costs on health care institutions due to readmissions in patients waiting for gall bladder disease surgery are high. Identifying patients at risk for these readmissions and offering them early laparoscopic cholecystectomy is very important. Keywords: Diseases, gall bladder, cholecystitis, gall stones, patient readmission, health care costs